2014
DOI: 10.1002/hep.27236
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine vascular endothelial growth factor signaling promotes cell proliferation and modulates sorafenib treatment efficacy in hepatocellular carcinoma

Abstract: Tumor cells express vascular endothelial growth factor (VEGF) that can activate VEGF receptors (VEGFRs) on or within tumor cells to promote growth in an angiogenesis‐independent fashion; however, this autocrine VEGF pathway has not been reported in hepatocellular carcinoma (HCC). Sorafenib, an angiogenic inhibitor, is the only drug approved for use in advanced HCC patients. Yet the treatment efficacy is diverse and the mechanism behind it remains undetermined. Our aims were to study the molecular mechanisms un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 30 publications
(63 reference statements)
3
61
0
Order By: Relevance
“…Peng et al [134] showed that tumor expression of VEGFR (phosphorylated VEGFR-1 and VEGFR-2) could affect the outcome of patients treated with sorafenib for advanced HCC [134] . Using immunohistochemistry analyzes, low pVEGFR-1 and pVEGFR-2 expressions in previously resected HCC specimens; a subsequent treatment with sorafenib was associated with worse outcome and poorer OS.…”
Section: Tissue Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Peng et al [134] showed that tumor expression of VEGFR (phosphorylated VEGFR-1 and VEGFR-2) could affect the outcome of patients treated with sorafenib for advanced HCC [134] . Using immunohistochemistry analyzes, low pVEGFR-1 and pVEGFR-2 expressions in previously resected HCC specimens; a subsequent treatment with sorafenib was associated with worse outcome and poorer OS.…”
Section: Tissue Biomarkersmentioning
confidence: 99%
“…Using immunohistochemistry analyzes, low pVEGFR-1 and pVEGFR-2 expressions in previously resected HCC specimens; a subsequent treatment with sorafenib was associated with worse outcome and poorer OS. The authors postulated that high autocrine VEGF signaling activity in tumor tissue could be predictive of response and outcome in patients treated with sorafenib [134] . These results could be hampered somewhat by the retrospective feature of the analysis, the small number of patients included and the low feasibility in clinical practice.…”
Section: Tissue Biomarkersmentioning
confidence: 99%
“…The PLCγ1-ERK1/2 pathway is well recognized as an important pathway that modulates cell proliferation in some malignant tumors [27][28]. To determine whether this pathway was the mechanism underlying HOP regulation of GC cell growth, we evaluated the expression of PLCγ1 and ERK1/2 by western blotting.…”
Section: Autocrine Hop Signaling Promoted Cell Proliferation Through mentioning
confidence: 99%
“…Our analysis also identified CRP as one of the independent prognostic markers which led to construction of a pretreatment scoring system based on CRP, AFP, albumin and major vascular invasion for the stratification of the prognosis of patients with advanced HCC treated by sorafenib. Several candidate biomarkers or genetic signatures have been reported for predicting the prognosis [35][36][37][38][39], but they are costly and not readily available. In contrast, the serum CRP level is examined routinely in clinical practice, and it does not require invasive tissue collection.…”
Section: Discussionmentioning
confidence: 99%